THE ROLE OF MEDICAL WORKERS IN PREVENTION AND PROMOTING A HEALTHY LIFESTYLE (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
This article examines the concept of health, its fundamental medical principles, and the professional and social role of healthcare workers in implementing these principles. Drawing upon the definition of health provided by the World Health Organization, the article highlights the significance of principles such as prevention, hygiene, early diagnosis, mental well-being, and medical ethics. Furthermore, the therapeutic, rehabilitative, educational, and ethical activities of healthcare workers are analyzed as an integral part of the healthcare system